2000
DOI: 10.1161/01.hyp.35.4.992
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of AT 1 and ET A Receptor Blockade in a Transgenic, Angiotensin II–Dependent, Rat Model

Abstract: Abstract-Angiotensin II and endothelin may participate in increasing blood pressure and inducing end-organ damage, but the evidence is conflicting. We tested the hypothesis that endothelin A receptor blockade would ameliorate blood pressure and end-organ damage in a rat model of human renin-dependent hypertension. We studied rats that were transgenic for both the human renin and angiotensinogen genes. Experimental groups (nϭ12 each) of untreated transgenic rats, transgenic rats receiving subdepressor doses of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
3
25
0
Order By: Relevance
“…Whereas some authors reported that ET A blockade lowers BP in various hypertensive models, ie, in Sabra salt-sensitive rats, 29 DOCAsalt rats, 30 salt-loaded SHR-SP, 31 or rats transgenic for human angiotensinogen and renin genes. 32 Rothermund et al 10 did not find a protective effect of ET A blockade in heterozygous Ren-2 animals. Although quite opposite to our findings, their results could be explained by different timing of the experiments, ie, different age of animals, and by using heterozygous instead of homozygous animals.…”
Section: Discussionmentioning
confidence: 94%
“…Whereas some authors reported that ET A blockade lowers BP in various hypertensive models, ie, in Sabra salt-sensitive rats, 29 DOCAsalt rats, 30 salt-loaded SHR-SP, 31 or rats transgenic for human angiotensinogen and renin genes. 32 Rothermund et al 10 did not find a protective effect of ET A blockade in heterozygous Ren-2 animals. Although quite opposite to our findings, their results could be explained by different timing of the experiments, ie, different age of animals, and by using heterozygous instead of homozygous animals.…”
Section: Discussionmentioning
confidence: 94%
“…65 A number of preclinical studies have established that dual blockade of AT 1 and endothelin receptors results in greater blood pressurelowering effects than does the blockade of either receptor alone. [66][67][68][69] An early series of dual AT 1 and ET receptor antagonists was described by Merck, 70 following the recognition of structural and functional similarities between the endothelin and AT 1 receptors, and similar structure-activity relationships seen for their peptide agonist ligands. A starting point for the discovery of bifunctional AT 1 /ET A antagonists was the existing Merck library of compounds blocking the AT 1 receptor.…”
Section: Next Generation Arbs That Block Endothelin Receptorsmentioning
confidence: 99%
“…The findings document the observation that Ang II-induced cardiac injury is in part mediated by ET-1-related mechanisms. 3,4 We were surprised that long-term ECE inhibitor treatment did not ameliorate renal damage. We showed earlier that the ET A/B receptor blocker bosentan effectively reduced cardiac and renal damage.…”
Section: Muller Et Al Ece Inhibition and Ang Ii-induced Cardiac Damagmentioning
confidence: 99%